Effect of epoxidized natural rubber on thermal properties, fatigue life, and natural weathering test of styrene butadiene rubber/recycled acrylonitrile-butadiene rubber (SBR/NBRr) blends - Nik Noriman, Zulkepli, Dr.; Hanafi, Ismail, Prof. Dr. (John Wiley & Sons, Inc., 2013)
Link to publisher's homepage at http://onlinelibrary.wiley.com/